2023
DOI: 10.1039/d3qm00215b
|View full text |Cite
|
Sign up to set email alerts
|

An AIE-active type I photosensitizer based on N,N′-diphenyl-dihydrophenazine for high-performance photodynamic therapy under hypoxia

Abstract: Type Ⅰ PDT has been demonstrated to be superior over type Ⅱ PDT due to its better hypoxia tolerance. Nowadays, photosensitizers (PSs) featuring type Ⅰ active free radicals (O2-·, ·OH)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…21 Besides, in our previous studies, DHP-based cyanine dyes showed promising results for an AIE-active type I photosensitizer. 22 However, the construction of D–A structure photosensitizers by combining DHP as a strong electron-donating unit (D) with electron acceptors (A) has not been studied systematically.…”
Section: Introductionmentioning
confidence: 99%
“…21 Besides, in our previous studies, DHP-based cyanine dyes showed promising results for an AIE-active type I photosensitizer. 22 However, the construction of D–A structure photosensitizers by combining DHP as a strong electron-donating unit (D) with electron acceptors (A) has not been studied systematically.…”
Section: Introductionmentioning
confidence: 99%